Robotic vs. 3D laparoscopic resection for rectal cancer: a single-center retrospective study of short-term outcomes and functional recovery - Liu, Dunbo; Zhang, Qianshi; Guo, Fangliang; Sun, Zhiwei; Ren, Shuangyi (Frontiers in Surgery, 2025)
BackgroundWithin the evolving landscape of precision medicine, robot-assisted surgery has emerged as a valuable tool in rectal cancer management. However, comprehensive evidence regarding its safety and clinical efficacy remains limited.MethodsThis retrospective study analyzed 235 patients with middle and low rectal cancer who underwent surgical resection from January 2020 to March 2023. Comprehensive perioperative data, including baseline characteristics, intraoperative parameters, and postoperative outcomes, were systematically collected and analyzed. The International Prostate Symptoms Score, International Erectile Function Index, and Female Sexual Function Index were utilized to assess postoperative organ function recovery. Multivariable logistic regression analysis was performed to identify predictors of functional recovery and postoperative complications. All patients were prospectively followed for up to 3 years, with survival outcomes evaluated using Kaplan–Meier analysis.ResultsRobotic surgery demonstrated significantly longer operative duration compared to 3D laparoscopic surgery (162.0 ± 44.0 vs. 149.0 ± 41.0 min, p < 0.05), yet resulted in significantly reduced intraoperative blood loss (51.0 ± 34.0 vs. 63.0 ± 43.5 ml, p = 0.010), albeit with substantially higher procedural costs (93,808 ± 1,334 vs. 71,863 ± 1,220 yuan, p < 0.05). Notably, the robotic approach yielded superior lymph node retrieval, facilitated earlier detection of pathological stages, promoted enhanced recovery of urogenital function, and was associated with a reduced incidence of severe postoperative complications. Multivariable analysis revealed that robotic surgery was an independent predictor of improved urinary function recovery at 3 months (OR = 3.45, 95% CI: 1.82–6.54, p < 0.001) and enhanced sexual function recovery at 6 months (male: OR = 2.89, 95% CI: 1.41–5.93, p = 0.004; female: OR = 3.12, 95% CI: 1.23–7.89, p = 0.017). Both surgical approaches demonstrated comparable baseline characteristics and long-term survival outcomes (p > 0.05).ConclusionRobotic surgical systems demonstrate comparable safety and efficacy to traditional laparoscopy for rectal cancer resection, while offering distinct advantages including reduced intraoperative bleeding, improved pathological staging accuracy, and accelerated postoperative recovery of urinary and reproductive function. Both procedures exhibit similar short-term efficacy and safety profiles, with no significant difference in long-term survival rates.